Developing a classification of living things e-module with a jelajah alam sekitar approach to help students reduce misconceptions and strengthen scientific literacy - Illah , Khofiatul; Amelia, Rizki Nor (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
One strategy to reduce misconceptions and strengthen science literacy in the classification of living things is to facilitate students with contextual learning resources. Therefore, this study aims to develop an e-module as a learning resource that is integrated with the approach of Jelajah Alam Sekitar (JAS) so as to enable students to understand science concepts through collaborative practices of nature exploration. This research method is research and development using the 4D development model (define, design, develop, and disseminate). Class VII students at MTs Ishthifaiyah Nahdliyah were involved as samples with details of 180 students as the standardization test sample of the integrated science misconception-literacy instrument, 29 students as the e-module readability sample, and 32 students as the e-module implementation sample.  Data collection was carried out using interviews, a questionnaire, and student science literacy and misconception tests. The instruments used included interview guidelines, e-module characteristic questionnaires, e-module feasibility questionnaires, student response questionnaires, and pretest-posttest questions. Data analysis for the effectiveness of the e-module on student science literacy and misconceptions was performed using a paired t-test. The developed JAS E-module proved to be very feasible in terms of material concept, presentation, language, and graphics, and had excellent characteristics in terms of module characteristics, JAS components, and activities that contained indicators of misconceptions and science literacy. In addition, based on the results of the effectiveness test, in general, the e-module proved significant in reducing misconceptions (p<.05; t=-4.818; df=31) and strengthening students' science literacy (p<.05; t=4.636; df=31). Thus, this development contributes to improving science learning, especially in reducing misconceptions and strengthening science literacy.